Awareness on root canal treatment among patients attending dental clinic in Kuantan, Pahang - Mat Daud, Muhamad Sharifuddin; Ruslan, Suhaili; Isa, Siti Syahirah; Abllah, Zurainie (Elsevier, 2019)
Root Canal Treatment (RCT) is a treatment to save a tooth so that it can retain and function but most people are not aware about it. A total of 200 respondents attended Kulliyyah of Dentistry, IIUM (age: 16-60 years old) completed self-administered questionnaire. 57% of the respondents have high level of awareness of RCT. Female gender, people with good oral hygiene practice and people that had past experienced of tooth symptoms had higher awareness on RCT. Despite the findings, more strategies needed to be implemented to increase the knowledge on RCT as it is the main barrier for getting RCT.